Mit digitalen Hebeln zur Kreislaufwirtschaft: Mit digitalen Hebeln zur Kreislaufwirtschaft - Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Nachhaltige Industrie)

Prompt Engineering im Systems Engineering - Hovemann, Aschot; Bita, Isaac Mpidi; Aldade, Abed Alrahman; von Heißen, Oliver; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Große Sprachmodelle wie GPT-4 bieten erhebliche Potenziale für das Systems Engineering. Prompt-Engineering ermöglicht einen flexiblen Einsatz im Anforderungsmanagement, Systementwurf und in der Integration, Verifikation und Validierung ohne aufwendiges Modelltraining. Die Formulierung von Prompts und die Anwendung fortschrittlicher Techniken erfordern jedoch tiefes Domänenwissen. Der Beitrag zeigt Potenziale und Herausforderungen dieser Technik auf und illustriert praktische Anwendungsbeispiele

Advanced Analytics Capability Map for Smart Factories: Supporting the Planning, Design, Management and Operations of Advanced Analytics Use Cases - Weller, Julian; Lick, Jonas; Brock, Jonathan; Heuwinkel, Tim; Hartmann, Stefan; Kühn, Arno; von Enzberg, Sebastian; Dumitrescu, Roman (Procedia CIRP)

Product Management: Tasks, Roles, and the Importance of Data - Grigoryan, Khoren; Martin, Lucas; Lamarz, Jessica; Fichtler, Timm; Hohn, Bennett; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Untangling circular value networks - mechanisms, advantages, risks, and future research - Petzke, Lisa Irene; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

A serious game to introduce Systems Engineering in interdisciplinary teams - Könemann, Ulf; Niemeyer, Marcel; Schierbaum, Anja; Dumitrescu, Roman (Procedia CIRP)

Assessing and Communicating Software Security: Enhancing Software Product Health with Architectural Threat Analysis - Strüwer, Jan-Niclas; Trentinaglia, Roman; Wohlers, Benedict; Bodden, Eric; Dumitrescu, Roman (AHFE International)
Assessing and communicating software security has become a crucial concern in the era of digital transformation. As software systems grow more complex and interconnected, it becomes increasingly challenging to effectively evaluate and communicate a product's security status to both technical and non-technical stakeholders. The Software Product Health Assistant (SPHA) is designed to automatically collect and aggregate data from existing expert tools and derive, among other scores, a transparent Security Score. SPHA is designed to present and explain this Security Score to decision-makers to support their responsibilities. In this paper, we demonstrate how to integrate data from SMARAGD (System Modeler for Architectural Risk Assessment and Guidance on Defenses), a safety-informed threat modeling tool, into SPHA to enhance the existing definition of its Security Score. To achieve this, we combine information about known vulnerabilities with architectural and threat data to calculate a realistic risk score for the product in question.

SmartHomeFarming: Trends, Challenges, and Solutions in a Digital and Sustainable Future - Bita, Isaac Mpidi; Hermelingmeier, Dominik; Gröger, Stefan; Hovemann, Aschot; Pfeifer, Stefan; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Procedia CIRP)

Towards a hybrid theory: Derivation of a view concept between Model-based Systems Engineering and Data Analytics - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Maker Systems Engineering Systematic: A Practitioner-Driven Research Agenda - Hermelingmeier, Dominik; Bita, Isaac Mpidi; Menne, Leon; Jobelius, Johannes; Tichonov, Denis; Pfeifer, Stefan; Dumitrescu, Roman (Procedia CIRP)

Success Factors in Product Management and the Role of Data - Fichtler, Timm; Petzke, Lisa Irene; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

The Nexus Model: Towards a metamodel for data-driven system models - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Procedia Computer Science)

Linking Abstract Digital Twin Data to 3D Models: A Configurable Approach for Real-Time Adaptation - Eckertz, Daniel; Sander, Mattes; Masroor, Omar; Dumitrescu, Roman (2025 8th International Conference on Information and Computer Technologies (ICICT))

Advanced Systems Engineering - Auswertung des Gesamtbildes ASE - Aktueller Stand zum Ende von AdWiSE - Dumitrescu, Roman; Albers, Albert; Gausemeier, Jürgen; Riedel, Oliver; Lindow, Kai (Forschungsberichte Pflichtabgabe (BMFTR, BMWE…))

AI-Augmented Model-Based Systems Engineering - Bernijazov, Ruslan; Dumitrescu, Roman; Hanke, Fabian; von Heißen, Oliver; Kaiser, Lydia; Tissen, Denis (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract The increasing complexity of modern technical systems necessitates innovative approaches such as Model-Based Systems Engineering (MBSE). In this context, using Artificial Intelligence (AI) emerges as a key enabler for practical application and efficiency improvement. This article introduces a maturity model for AI-based assistance systems in MBSE. It helps companies assess their current automation level in MBSE activities, providing a foundation for strategic planning of process improvements.

Advanced Analytics in Smart Factories: Towards an actionable Taxonomy for Prescriptive Analytics Use Cases - Weller, Julian; Nalavade, Sumit; Gmelch, Oliver; Migenda, Nico; Heuwinkel, Tim; Dumitrescu, Roman (Procedia CIRP)

Evaluation Of The Challenges In Implementing AI Across The Different Phases - Empirical Insights Derived From AI Implementation Projects In Industry - Dondorf, Verena; Happe, Leonie; Hobscheidt, Daniela; Kürpick, Christian; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics : CPSL 2025)

Generating An Automated Assembly Graph On The Basis Of The 3D-Geometry Of A Product Assembly Group - Disselkamp, Jan-Philipp; Lick, Jonas; Azem, Ghayth; Grothe, Robin; Ptock, Lukas; Meyer, Matthias; Kürpick, Dominik; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics: CPSL 2025)

Case Study For Introducing Digital Cardboard Engineering - Disselkamp, Jan-Philipp; Lick, Jonas; Ptock, Lukas; Zacke, Julian; Wilk, Marcel; Ostendorf, Jona; Meyer, Matthias; Westphal, Svenja; Kürpick, Dominik; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Conference on Production Systems and Logistics : CPSL 2025)

Is explaining more like showing or more like building? Agency in metaphors of explaining - Porwol, Philip Fabian; Scharlau, Ingrid (Frontiers in Psychology)
Explanations play a crucial role in knowledge transfer and meaning-making and are often described as a co-constructive process in which multiple agents collaboratively shape understanding. However, the metaphors used to conceptualize explaining may influence how this process is framed. This study investigates the extent to which the co-constructive nature of explaining is represented in explaining metaphors. Using a systematic analysis of agency, we examined how these metaphors depict the explanation process and the roles of the agents involved. We found that explaining metaphors lack collaboration between explainer and addressee, constructiveness of the process, as well as bidirectionality and iterativeness. In light of current research on metaphorical framing, the study thus highlights the risk that such explaining metaphors may reinforce a non-co-constructive perspective on explaining and a top-down approach in the development of AI systems as well as other areas.